PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN EKOWISATA DI DESA HUTA GINJANG, KECAMATAN SIANJUR MULA-MULA, KABUPATEN SAMOSIR, PROVINSI SUMATERA UTARA (PUBLIC PERCEPTION OF ECOTOURISM DEVELOPMENT IN HUTA GINJANG VILLAGE, SIANJUR MULA-MULA SUB-DISTRICT,SAMOSIR - Benmart E. Manalu; Siti Latifah; Pindi Patana (Peronema Forestry Science Journal, 2013)
This research aimed to examine the potential of ecotourism and public perception of ecotourism development in the village of Huta Ginjang, District Sianjur Early, Samosir Regency. To assess the potential of ecotourism is done by observation. While the public perception through questionnaires and interviews. The results showed that the village of Huta Ginjang has natural and cultural potency that can be developed as ecotourism appeal. It is also supported by the public perception that states that peoples agree on the development of ecotourism in the village of Huta Ginjang. Keywords: ecotourism, public perceptions of ecotourism development, Huta Ginjang Village.